The Kelantan Mak Yong: Dancing Towards a Compromise Between Culture and Religion - Sripaoraya, Kanit (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Throughout the timeless centuries before the modern era, the people of the proud state of Kelantan enjoyed ‘Mak Yong,’ a traditional form of entertainment. The ‘Mak Yong’ performance brought the people together to view this folk dance-drama, largely because it was created by their ancestors and represented continuity and cultural heritage. This dance also served to heal illness, performed by mixed-gender entertainers. Significantly, this authentic performance was worldly inscribed in 2008 on the UNESCO Representative List of the Intangible Cultural Heritage of Humanity. However, due to the interpretation of the politicized religious aspect of Kelantan state government, this performance was reconstructed by eliminating the female components. The new form of male Mak Yong was created. This research aims to discuss the contemporary issue of Kelantan Mak Yong and to propose the safeguarding method that compromises between culture and religion by reflecting the lessons learned from three participation anthropological fieldworks as a Mak Yong practitioner, a traditional dance-drama researcher, and a traditional dance-drama lecturer from 2014 until the present day. This study applied multi-disciplinary approaches such as performing arts and dance studies, anthropology, and gender analysis to investigate and collect the data. The results found that, instead of eliminating the female components, Kelantan Mak Yong can be utilized as a means for cultivating gendered behaviour, inculcating the religious doctrine, transmitting the moral-coded, and enhancing self-empowerment for Kelantan society by incorporating the guideline of the state arts policy (Dasar Kesenian Kelantan) to the performance’s components.